Linhas de produção do TDAH: uma cartografia das práticas de um serviço universitário de saúde em Belém-PA - CRUZ, Bruna de Almeida (2016)
This study aimed to investigate the practices in course on a university public health service from Belém-PA, attempting to follow some lines of the attention deficit and hyperactivity disorder (ADHD) diagnosis elaboration. Such nosological category has gained popularity in the specialized literature, implying an increasing number of diagnosed cases in Brazil and other countries. In addition, the expansion of markets in order to sustain the diagnosis and its treatment is also remarkable, as an effect of successive reviews of diagnostic manuals, increasingly widespread, and an equipping of health and education services, which cooperate in their identification and treatment. Therefore, a problematizing analysis of the production of these supposed disorders was undertaken, articulating dialogues with the aid of the critical literature about life medicalization processes and standardization of differences. This research considers the construction of that diagnosis in the materiality in which it occurs on a public children and youth health service, linked to one of the university hospitals of UFPA. From a genealogical perspective with cartographic orientation, we seek to give visibility to power lines operating in the construction of the diagnostic. It was made an option for multiple strategies to produce informations in this search, including: documents from the service, between them, registers of diagnosed clients or with the diagnostic hypothesis about which concerns this study; field diaries on the visits to the service, as well as collective interview with professionals involved in the production of diagnosis. The analysis of the documental set produced in this research has been developed into the following series of practices: “ADHD as a scientific fact”, “diagnostic practices and tools”, “combinations of nosological categories”, “effort for integral care in the diagnostic service”, “surveillance and protection of child development”, “ADHD relation with the school complaint”, “redemptive and for citizenship effects of the report”, “production of markets for therapies consumption” and “resistance face to drugs prescription”. The analysis suggests that ADHD is undoubtedly not a mere nosological category, being involved with tangled lines of control and subjectivation of the population, so that the diagnosis operates the maintenance of these lines and the normalization of deviant, like a scapegoat in this process.